2014
DOI: 10.1074/jbc.m113.527416
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Malondialdehyde-modified Proteins by the C Terminus of Complement Factor H Is Mediated via the Polyanion Binding Site and Impaired by Mutations Found in Atypical Hemolytic Uremic Syndrome

Abstract: Background: Malondialdehyde (MDA) released during oxidative stress modifies proteins covalently. Results: The C terminus of complement regulator factor H binds negative patches on MDA-modified proteins, and aHUSrelated mutations affect the interaction. Conclusion: Defects in factor H binding to MDA-modified surfaces might allow deleterious complement activation on them. Significance: MDA-modifications are potentially a new factor in aHUS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Several studies have examined the functional consequences of the 402 SNP in the context of full‐length FH, FHL‐1, the isolated CCP7 domain, or partial FH fragments entailing CCP6‐8. These studies have shown that the Y402H SNP results in modified binding to several ligands such as GAGs, C‐reactive protein, zinc ions, the extracellular matrix protein fibulin 3, and oxidation end‐products, with many of these findings generating controversy among the different reports. Remarkably, these studies have revealed that the differential binding properties of the Y402H variant are pronounced when the mutation is studied in the context of isolated, recombinant fragments of FH.…”
Section: Insights Into Fhl‐1 Functionmentioning
confidence: 99%
“…Several studies have examined the functional consequences of the 402 SNP in the context of full‐length FH, FHL‐1, the isolated CCP7 domain, or partial FH fragments entailing CCP6‐8. These studies have shown that the Y402H SNP results in modified binding to several ligands such as GAGs, C‐reactive protein, zinc ions, the extracellular matrix protein fibulin 3, and oxidation end‐products, with many of these findings generating controversy among the different reports. Remarkably, these studies have revealed that the differential binding properties of the Y402H variant are pronounced when the mutation is studied in the context of isolated, recombinant fragments of FH.…”
Section: Insights Into Fhl‐1 Functionmentioning
confidence: 99%
“…Additional ligands of FH include markers of oxidative stress, such as malondialdehyde (MDA) and malondialdehyde acetaldehyde (MAA) [121123], and serum apolipoprotein E (ApoE) [124]. For example, FH is a major MDA-binding protein that interacts via CCPs 7 and 20 (see Fig.…”
Section: Other Ligands Of Factor Hmentioning
confidence: 99%
“…The assays that analyzed competition of FH binding by FH fragments were performed with 10 mM FH19-20 or 100 mM FH6-8. 29 To set up a calcein-release assay, HUVECs (3 3 10 6 in gelatin-PBS) were incubated with 25 mM calcein AM (BD Pharmingen) at 37°C for 30 minutes, followed by washing. Cells (1 3 10 4 ) were incubated with anti-CD59 antibody (0 to 0.13 mM) in 15% NHS for 15 minutes.…”
Section: Endothelial Cell Assaysmentioning
confidence: 99%